Telemedical Support in Patients with Chronic Heart Failure: Experience from Different Projects in Germany. (18th July 2010) - Müller, Axel; Schweizer, Johannes; Helms, Thomas M.; Oeff, Micheal; Sprenger, Claudia; Zugck, Christian
Abstract : The great epidemiological significance and costs associated with chronic heart failure pose a challenge to health systems in Western industrial countries. In the past few years, controlled randomised studies have shown that patients with chronic heart failure benefit from telemedical monitoring; specifically, telemonitoring of various vital parameters combined with a review of the symptoms, drug compliance and patient education. In Germany, various telemedical monitoring projects for patients with chronic heart failure have been initiated in the past few years; seven of them are presented here. Currently 7220 patients are being monitored in the seven selected projects. Most patients (51.1%) are in NYHA stage II, 26.3% in NYHA stage III, 14.5% in NYHA stage I and only 6.6% in NYHA stage IV respectively. Most projects are primarily regional. Their structure of telemedical monitoring tends to be modular and uses stratification according to the NYHA stages. All projects include medical or health economics assessments. The future of telemedical monitoring projects for patients with chronic heart failure will depend on the outcome of these assessments. Only of there is statistical evidence for medical benefit to the individual patient as well as cost savings will these projects continue.